1991
DOI: 10.1159/000112194
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Beta Cells of the Islets of Langerhans is Further Questioned by the Expression of Neuronal Intermediate Filament Proteins, Peripherin and NF-L, in the Rat Insulinoma RIN5F Cell Line

Abstract: Intermediate filament proteins of the rat insulinoma RIN5F cell line were characterized. Two-dimensional gel analysis followed by immunostaining of proteins demonstrated that these cells express both peripherin and the low-molecular-mass neurofilament protein (NF-L); this was confirmed for peripherin by immunohistochemistry, peptide analysis and Northern blot. No expression of these proteins could be detected with these same methods either in the adult pancreas or in the tumor at the origin of the cell line, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 28 publications
2
25
1
Order By: Relevance
“…In nerve cells, NFs determine axon caliber, thus influencing the speed of vesicle transport and action potential conduction [1]. Although the expression NFs in non-neuronal cells has also been reported [2,3,4], a specific function has not been established. In particular, the expression of NFs in the anterior pituitary (AP) has been a subject of some controversy [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In nerve cells, NFs determine axon caliber, thus influencing the speed of vesicle transport and action potential conduction [1]. Although the expression NFs in non-neuronal cells has also been reported [2,3,4], a specific function has not been established. In particular, the expression of NFs in the anterior pituitary (AP) has been a subject of some controversy [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Peripherin can be found in islet ␤ cells of mouse embryonic pancreas using histochemistry procedures, but its production in the islets of pancreas of adult mice decreases until becoming undetectable using these same procedures (9). In our previous study (16), hybridoma screening was conducted on cryosections of pancreata from adult NOD.RAG-2 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these autoantigens are found not only in pancreatic ␤ cells, but also in cells from the nervous system (7). In fact, islet ␤ cells and neurons share several phenotypical similarities, thus suggesting the same ectodermic origin (8,9). Moreover, the hypothesis of a sole autoimmune response against islet ␤ cells in T1D is controversial because several studies have demonstrated that the pancreatic nervous system is also affected by the autoimmune response during the development of T1D (10 -12).…”
mentioning
confidence: 99%
“…In the adult, comparison between NF-L and peripherin immunoreactivities shows that peripherin expression is more restricted than that of NF-L and remains limited to the neurons in which it is expressed during development, i.e., motor neurons, all sensory neurons irrespective of their origin (neural tube, neural crest, or placodes), and sympathetic neurons (Parysek and Goldman, 1988;Escurat et al, 1990;Portier et al, 1993). As with other neuronal proteins (Eisenbarth et al, 1982;Pol& et al, 1984Pol& et al, , 1993Wiedenmann et al, 1986;Teitelman and Lee, 1987), it is also transiently expressed during ontogenesis in the adrenal medulla and in the pancreas (Escurat et al, 1991b). It is clear, from all observations concerning peripherin expression during development, that this protein is expressed in postmitotic neuroblasts that have reached their final destination and extend neurites.…”
Section: Introductionmentioning
confidence: 94%